دور رقمنة الخزينة العمومية في تفعيل الرقابة على نفقات التسيير: دراسة حالة الخزينة العمومية بالأغواط - سكحال سعاد; مخلوفي عزوز (جامعة عمار ثليجي -الأغواط, 2022)
The Algerian government is working to improve the public service and preserve by digitizing the administration and using modern technological means and attempting to test to which extent it impacts the activation of control process especially in governmental financial institutions. The public treasury is considered one of the most prominent public bodies of a financial nature that works to pay expenses and collect public revenues. The latter also has a control over all expenses, wether they are related to operating expenses, equipment or investment, before implementing any payment process, and this is through a thorough and comprehensive examination of all justification documents .and proofs In this regard, we wanted to address, through our research, the issue of the role of digitizing the public treasury in activating the control over the expenses (case study of the state treasury of laghouat) and we highlighted through it: What is electronic management (digitization), and the role of public accounting in controlling the management expenses in addition to our assessment of the extent to which the digitization of the public treasury contributes to activating the control process over management expenses, and this is through the applied study that we carried, out before and after the implementation of digitization and through which we tracked management expenses from the entrance of its access to the public treasury until the exit. Key words: electronic administration-(digitization)–public treasury-the control- management expenses